ANALISIS PEMBIAYAAN DAN KREDIT SEKTOR KONSTRUKSI DI INDONESIA: STUDI PERBANKAN SYARIAH DAN KONVENSIONAL - Nidaa Nazaahah Kusumawati; Nunung Nuryartono; Irfan Syauqi Beik (IPB University, 2017)
The construction sector is an important sector in supporting development projects in Indonesia. The development of the construction sector requires the role of the banking sector to provide access of capital through credit or financing. This study aims to analyze the factors affecting construction financing and credit in Islamic and Conventional Banking in Indonesia and among regions in Indonesia. This study uses Vector Autoregression/ Vector Error Correction Model (VAR/VECM) with monthly data from 2006 until 2014 and panel data analysis with yearly data from 2009 until 2013. The study results that the factors affecting financing and credit on Construction Sector in Indonesia are Third Party Funds (DPK), Wholesale price index, fee of SBIS (interest rate of SBI), percentage of Non Performing Financing (Non Performing Loan), Consumer Price Index and equivalent rate of financing (Interest rate of Credit). Furthermore, the factors affecting financing and credit on Construction Sector among regions in Indonesia are Third Party Funds, Gross Domestic Regional Product of Construction Sector, Gross Domestic Regional Product per Capita and percentage of Non Performing Financing (Non Perfoming Loan). Keywords: Construction, Credit, Financing, Panel data, VAR/VECM